المناخ المدرسي وعلاقته بالحاجات الارشاديه لدى التلاميذ المتفوقين في مرحلة المتوسط - آمال بوطيب; لبنى قدور (جامعة الوادي - University of Eloued, 2025)
"ملخص الدراسة: لقد تطرقنا في دراستنا هذه إلى موضوع المناخ المدرسي وعالقته بالحاجات اإلرشادية لدى التالميذ المتفوقين في المرحلة المتوسطة. حيث هدفت هذه الدراسة للكشف عن العالقة االرتباطية بينهما حيث تمثل المتغيرين في مقياسين هما مقياس خاص بالمناخ المدرسي ومقياس االخر خاص بالحاجات اإلرشادية وهذا على عينه قدرها )80( تلميذا وتلميذا في المرحلة التعليم المتوسط مكونة من ستون )60( إناث وعشرون )20( ذكور مقسمة على مجموعة من المتوسطات خمسة )5( متوسطات في والية المغير وثالثة متوسطات )3(والية الوادي وتم اتباع المنهج الوصفي االرتباطي في هذه الدراسة، ثم تمت معالجة البيانات باستخدام المعالج اآللي Spss نسخة 25 وتم استخدام األساليب االحصائية معامل ارتباط بيرسون واختبار ت لحساب الخصائص السيكومترية، توصلت هذه الد ارسة في نتائج الفرضية العامة إلى عدم وجود عالقة ذات داللة احصائية بين المناخ المدرسي والحاجات اإلرشادية لدى التالميذ المتفوقين في المرحلة المتوسطة أما بالنسبة للفرضيات الجزئية توصلت إلى: ـ عدم وجود فروق ذات داللة إحصائية في المناخ المدرسي لدى التالميذ المتفوقين في المرحلة المتوسطة تعزى لمتغير الجنس. ـ عدم وجود فروق ذات داللة احصائية في الحاجات اإلرشادية لدى التالميذ المتفوقين في المرحلة المتوسطة تعزى لمتغير الجنس. ""Abstract In this study, we addressed the topic of school climate and its relationship to the guidance needs of gifted students in middle school. This study aimed to reveal the correlation between them, as the two variables were represented by two scales: one for school climate and the other for guidance needs. This was done on a sample of (80) male and female students in the intermediate education stage, consisting of sixty (60) females and twenty (20) males, divided into a group of averages: five (5) averages in the state of El Meghair and three (3) averages in the state of El Oued. The descriptive correlational approach was followed in this study, and the data were then processed using the automated SPSS program, version 25. Statistical methods, including the Pearson correlation coefficient and the t-test, were used to calculate psychometric properties. This study concluded, in the results of the general hypothesis, that there is no significant correlation between school climate and guidance needs among high- achieving students in the intermediate stage. As for the partial hypotheses, it concluded that: There are no statistically significant differences in the school climate among high-achieving students in the intermediate stage attributable to the gender variable. There were no statistically significant differences in the guidance needs of gifted middle school students attributable to gender."
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص تربية خاصة.
Keywords: الحاجات الإرشادية; المناخ المدرسي; التفوق; Excellence; school climate; and guidance needs.